The early church an annotated bibliography of literature in English - Robinson, Thomas Arthur, 1951- (Metuchen, NJ ATLA, 1993)
Includes bibliographical references and indexes.
Donated by the Australian College of Theology, 1996
Keywords: Church history -- primitive and early church, ca. 30-600 -- abstracts; Church history -- primitive and early church, ca. 30-600 -- indexes; Christian literature, early -- abstracts; Christian literature, early -- indexes; Theology -- early church, ca. 30-600 -- abstracts; Theology -- early church, ca. 30-600 -- indexes